HEALTHCARE FAILURE MODE AND EFFECT ANALYSIS DESIGN FOR INDONESIA HOSPITAL LABORATORIES: A LITERATURE REVIEW - Zhafirah Salsabila; Masyitoh Masyitoh; Amal Chalik Sjaaf; Lia Gardenia Partakusuma (Indonesian Journal of Health Administration, 2021)
Background: Error rate in medical laboratories is very low. Only one error is identified every 330–1,000 events. The goal of laboratory services should outweigh patient safety in a well-structured manner. Healthcare Failure Mode and Effect Analysis (HFMEA) is a proactive preventive method for identifying and evaluating potential failure.Aims: This study identified factors affecting patient safety in hospital laboratories and described potential risk identification process using the HFMEA.Methods: This study was conducted between March-July 2020 and retrieved data from PubMed, Scopus, and Google Scholar. The data were generalized and extracted into Table 2 based on factors dealing with patient safety in hospital laboratories. This study performed a risk identification design based on the steps of HFMEA.Results: Out of 4,062 articles collected, only 8 articles between 2013–2020 were included for analysis. The highest error rate in laboratories occurred in the pre-analytic phase (49.2%–84.5%). The errors included clotted and inadequate specimen volume, and thus the specimens were rejected. Factors related to patient safety in laboratories were patient condition, laboratory staff performance (including training, negligence, and burnout), facilities, and accreditation.Conclusion: The HFMEA process used the result of hazard analysis with severity and probability criteria categorized into health sector. Decision tree analysis could determine the next step of the work process. The HFMEA must be adjusted to the equipment and technologies in each hospital laboratory. Leader’s commitment in monitoring and evaluation is required to maintain patient safety culture. More comprehensive data from Indonesian hospital laboratories are needed to generate more representative and applicable results.Keywords: error, HFMEA, laboratory, patient safety